Subcarrier grouping with environmental sensing for MIMO‐OFDM systems over correlated double‐selective fading channels. Issue 16 (3rd August 2016) - Lu, Jiaxun; Chen, Zhengchuan; Fan, Pingyi; Leatief, Khaled B.
Abstract: Multiple‐Input, Multiple‐Output (MIMO)‐orthogonal frequency division multiplexing (OFDM) is a promising technique in 5G wireless communications. In high‐mobility scenarios, the transmission environments are time‐varying and/or the relative moving velocity between the transmitter and receiver is also time‐varying. In the literature, most of previous works mainly focused on fixed subcarrier group size and precoded the MIMO signals with unitary channel state information. In this way, the subcarrier grouping may naturally lead to big loss of channel capacity in high‐mobility scenarios because of the channel state information difference on the subcarriers in each group. To employ the MIMO‐OFDM technique, adaptive subcarrier grouping scheme may be an efficient way. In this paper, we first consider MIMO‐OFDM systems over double‐selective i.i.d. Rayleigh channels and investigate the quantitative relation between subcarrier group size and capacity loss theoretically. With developed theoretical results, we also propose an adaptive subcarrier grouping scheme to satisfy the preset capacity loss threshold by adjusting grouping size with the sensed environmental information and mobile velocity. Theoretical analysis and simulation results show that to achieve a better system capacity, a sparse scattering, lower signal‐to‐noise ratio, and lower velocity as well as properly large antenna number are matched with larger subcarrier group size. One important observation is that if the antenna number is too large and higher than a threshold, which will not bring any additional gain to the subcarrier grouping. That is, the system capacity loss will converge to a lower bound expeditiously with respect to antenna number, which is given in theory also. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In high–mobility scenarios, the time–varying transmission environments and/or the relative moving velocity lead to fast time–varying channels. In this paper, adaptive subcarrier grouping scheme is designed to suit the fast time–varying multiple‐input multiple‐output orthogonal frequency division multiplexing channels. Theoretical and simulation results show that sparse scattering, lower SNR, and lower velocity as well as properly large antenna number are matched with larger subcarrier group size. In addition, higher antenna number will not bring additional gain to the subcarrier grouping size.